Phosphorylation of MeCP2 at Serine 80 regulates its chromatin association and neurological function. - Tao, J; Hu, K; Chang, Q; Wu, H; Sherman, N; Martinowich, K; Klose, R; Schanen, C; Jaenisch, R; Wang, W; Sun, Y (2009)
Mutations of MECP2 (Methyl-CpG Binding Protein 2) cause Rett syndrome. As a chromatin-associated multifunctional protein, how MeCP2 integrates external signals and regulates neuronal function remain unclear. Although neuronal activity-induced phosphorylation of MeCP2 at serine 421 (S421) has been reported, the full spectrum of MeCP2 phosphorylation together with the in vivo function of such modifications are yet to be revealed. Here, we report the identification of several MeCP2 phosphorylation sites in normal and epileptic brains from multiple species. We demonstrate that serine 80 (S80) phosphorylation of MeCP2 is critical as its mutation into alanine (S80A) in transgenic knock-in mice leads to locomotor deficits. S80A mutation attenuates MeCP2 chromatin association at several gene promoters in resting neurons and leads to transcription changes of a small number of genes. Calcium influx in neurons causes dephosphorylation at S80, potentially contributing to its dissociation from the chromatin. We postulate that phosphorylation of MeCP2 modulates its dynamic function in neurons transiting between resting and active states within neural circuits that underlie behaviors.